Trends in Personal Injury Litigation: the 1990s - Miller, John (Victoria University of Wellington Law Review, 2003)
Just as Accident Compensation did not exist in a political or social vacuum, it also did not exist in a legal vacuum. One of the remarkable features of the last decade has been the resurgence of personal injury actions, partially as a response to the scheme being perceived as less generous. John Miller details case law development over the last decade or so.